Law Enforcement Against Children as Perpetrators of the Crime of Theft with Violence (Case Study of Medan District Court Decision Number: 77/Pid.Sus-Anak/2023/PN Mdn) - Alti Laksana Simaremare; Kudadiri, Agnes Jessi; Handayani, Putri; Siahaan, Parlaungan Gabriel; Batu, Dewi Pika Lumban (Indonesian Journal of Advanced Research, 2023)
This research explores law enforcement against children as perpetrators of criminal acts of theft with violence through case study analysis of Medan District Court Decision Number: 77/ Pid.Sus – Anak /2023/ PN Mdn. The research method used is a qualitative descriptive research method with the proportion of research using library research. This is used to carry out analysis related to the issue being raised. The application of the law to Bayu Nugroho Karen, a child who is in conflict with the law as a perpetrator of the crime of theft with violence is in accordance with the provisions of the Criminal Procedure Code and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Where children can be held accountable for their actions and their rights as children who have committed criminal acts guaranteed in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System have been fulfilled in Decision number 77/Pid.Sus-Anak/2023/PN Mdn, dated 31 August 2023.